The Effectiveness Of Digital Media Mari Belajar On Human Movement System Material To Foster Curiosity Of Grade VI Elementary School Students - Anggraeni, Isnaeny Nurdiana; Utama, Candra; Winahyu, Sri Estu (Universitas Negeri Malang, 2024)
This study aims to assess the effectiveness of digital learning media